Potential, Challenges and Opportunities of Balinese Language in The Middle of Globalization Effects - Ni Luh Sukanadi; Ida Ayu Made Wedasuwari; Ni Wayan Eminda Sari; I G. A. Putu Tuti Indrawati (International Journal of Linguistics and Discourse Analytics, 2022)
Language is a component of nationalism, as stated in the youth oath “trilogy” which has been interpreted, among others, by "one language". The implementation of language politics, especially regarding the position and role of Indonesian and regional languages, cannot be separated from the history of the emergence of nationalism that has developed since the beginning of the 20th century. From the history of the development of the Indonesian language as a problem related to teaching, even the politics of language has been discussed by nationalist figures in Indonesia. Related to the issue of multiculturalism in Indonesian and regional languages ​​is very relevant in the current era of development reform. Balinese regional languages ​​have challenges ahead, especially in the face of global language competition. So the way out of facing these challenges is the development of a bilingual or multilingual concept. This concept can be seen in the structure of regional languages ​​where the use of regional languages ​​appears to be a bilingual situation. Indonesian language also appears in the concept of code switching, code mixing. So the use of the language has shifted to the system, not just code switching or code mixing. The opportunity for the Balinese language to survive, be nurtured and developed in the future will work well if there is a synergy of thought between the government, Balinese intellectuals, and Balinese people in developing the Balinese language